Detecting microorganisms producing surface active compounds in mangrove sediments in São Luís, Maranhão - Neto, Wallace Ribeiro Nunes; Ferreira, Romulo Maia; Monteiro, Joveliane De Melo; Lima, Jose Renato De Oliveira; Silva, Maria Raimunda Chagas; Araujo, Jessica Mayara Mendes; Silva, Darlan Ferreira da; Pachêco, Wallace Borges; Nunes Sobrinho, Pedro Paulo Barbosa; Monteiro, Andrea de Souza (Ciência e Natura, 2022)
Mangroves are areas of sediment transitions, favoring the cycling of materials associated with high concentration of microorganisms, presenting vulnerability to anthropogenic actions. The objective of this study was to evaluate the ability of microbiota in mangrove sediments of the Anil River, in the city of São Luís, Maranhão. To produce surface active compounds (SACs), samples were collected according to the EMBRAPA methodology by inoculating them in the Bushnell Haas medium, with carbon sources varying at 3% (v/v). From the production obtained, the supernatants of each culture were submitted to E24 analysis, drop spreading, thermal stability/pressure and pH variation. The SAC-producing species were identified using the MALDI-QTOF MS method. The producing species were identified as Serratia marcescens (2), Ochrobactrum spp. (3). E24 values ranged from 33% to 48% yield, with stability increase after autoclaving of 3% to 6% and of 17% for basic pH ranges, demonstrating the feasibility of using regional microorganisms present in mangroves to produce SACs from different carbon sources, as they have good rates of emulsification and stability to the diverse environmental factors.